The Language of Cyber Gender Anonymity on Hololive Virtual Youtubers - Kusuma Wijaya; Axlinabila Annisa Annasai; Annisa Deby Aulia; Rommel Utungga Pasopati (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
Hololive Production is a virtual YouTuber agency which accommodates 71 active talents (VTubers) with 65 million subscribers on YouTube. Hololive protects its talents’ privacy by giving them unreal names and avatars. Some viewers intend to find real identities of the talents, some others ignore the real personalities, while many of them keep secret although they know the real person behind the unreal avatar. Then, how is cyber gender anonymity characterized on the privacy of Hololive Virtual Youtubers? Using qualitative method, this article indicates necessity of cyber gender anonymity to keep Hololive’s talents’ identities safe. This is supported by Judith Butler’s posture of gender and Philip Zimbardo’s deindividuation. Unreal characters and names for VTubers are for anonymities but some viewers are doxing and making fun of them. Viewers want the streamers to be open and clear, but Hololive VTubers want to be anonymous and opaque. That idea contradicts sexual differences and gender anonymities that include tensions of being rigid and flexible. In conclusion, Hololive does not live static condition, but moves through ambiguous avatar of cyber anonymity. Anonymity could always be endangered; laws protect them but attacks to psychological condition is inevitable.